(untitled) (Research, Society and Development, 2022)
Background: The presence of weight regain (WR) and family support can impact the perception of Quality of Life (QOL) in the late postoperative period of bariatric surgery. It’s relevant to investigate the correlation between these factors. Objective: To test the association between perception of QOL, perception of family support and WR in women that had the bariatric surgery over more than 24 months. Method: Cross-sectional study carried out with 50 participants. Anthropometric data were collected and questionnaires were applied to assess the perception of quality of life and the perception and satisfaction with the post-surgical family support. Results: Satisfactory weight loss was observed after surgery. However, 46.0% of the sample had significant weight recurrence. Perception and satisfaction with family support after surgery were good. Participants had better perception of quality of life in domains related to physical aspects and worse scores in domains related to emotional aspects (p<0.000). The general emotional component and general physical component of quality of life were directly associated with the perception of family support and with the %PEP, and inversely associated with weight recurrence. Conclusion: It is important to encourage the family support during treatment after the bariatric surgery, to maintaining long-term multidisciplinary follow-up and monitoring of weight recurrence, in order to ensure the maintenance of the results achieved with the surgery and better of quality of life.